TRP Channels: Current Perspectives in the Adverse Cardiac Remodeling - Falcón, Debora; Galeano-Otero, Isabel; Calderón-Sánchez, Eva; Del Toro, Raquel; Martín-Bórnez, Marta; Rosado, Juan A.; Hmadcha, Abdelkrim; Smani, Tarik (Frontiers in Physiology, 2019)
Calcium is an important second messenger required not only for the excitation-contraction coupling of the heart, but it is also critical for the activation of signal transduction pathways responsible for the adverse cardiac remodeling and consequently for the heart failure. Sustained neurohumoral activation, pressure-overload, or myocardial injury can cause pathologic hypertrophic growth of the heart followed by interstitial fibrosis. The consequent heart’s structural and molecular adaptation might increase the risk of heart failure and malignant arrhythmia. Compelling evidences have demonstrated that Ca2+ entry through TRP channels might play pivotal roles in cardiac function and pathology. TRP proteins are classified into six subfamilies, TRPC (canonical), TRPV (vanilloid), TRPM (melastatin), TRPA (ankyrin), TRPML (mucolipin), and TRPP (polycystin), which are activated by numerous physical and/or chemical stimuli. TRP channels participate to the handling of the intracellular Ca2+ concentration in cardiac myocytes and are mediators of different cardiovascular alterations. This review provides an overview of the current knowledge of TRP proteins implication in the pathogenesis of some prevalent cardiac disorders associated with the adverse cardiac remodeling such as cardiac hypertrophy, fibrosis, and conduction alteration.